2017
DOI: 10.1016/j.molimm.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The complement system in age-related macular degeneration: A review of rare genetic variants and implications for personalized treatment

Abstract: HighlightsThe complement system plays a central role in age-related macular degeneration (AMD).Common and rare genetic variants in complement genes have been identified in AMD.Several of the rare variants affect the functioning of the complement system.However, a genetic association with AMD cannot always be proven.Functional assays can help identify patients for complement inhibiting therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
158
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(170 citation statements)
references
References 103 publications
1
158
1
4
Order By: Relevance
“…Three of the lowfrequency variants (p.Gln950His, p.Asn1050Tyr, p.Gln1143Glu) identified in CFH in aHUS/C3G patients, were previously reported to have a protective effect for AMD. 10 The p.Gln950His variant was detected in 15 aHUS/C3G patients, the p.Asn1050Tyr variant was detected in 21 aHUS/C3G patients, and the p.Gln1143Glu variant was detected in 9 aHUS/C3G patients.…”
Section: Genetic Variants Identified In Ahus/c3g and Amd Patientsmentioning
confidence: 96%
See 1 more Smart Citation
“…Three of the lowfrequency variants (p.Gln950His, p.Asn1050Tyr, p.Gln1143Glu) identified in CFH in aHUS/C3G patients, were previously reported to have a protective effect for AMD. 10 The p.Gln950His variant was detected in 15 aHUS/C3G patients, the p.Asn1050Tyr variant was detected in 21 aHUS/C3G patients, and the p.Gln1143Glu variant was detected in 9 aHUS/C3G patients.…”
Section: Genetic Variants Identified In Ahus/c3g and Amd Patientsmentioning
confidence: 96%
“…9,10 A number of low frequency protein-altering variants have been described to cause both aHUS/C3G and AMD, such as the p.Arg53His and p.Arg1210Cys variants in CFH, 11,12 p.Gly119Arg and p.Gly287Arg in CFI, 13,14 and p.Lys155Gln and p.Arg161Trp in C3. 10,15,16 A pathophysiologic explanation on how mutation in the same gene, in different patients, can lead to a different disease is not available. 1 It has been suggested that the final disease outcome is determined by the individual's overall genetic risk to each of these diseases, and is influenced by environmental factors.…”
mentioning
confidence: 99%
“…However, due to the extremely high level of sequence homology shared by all of the FHR proteins 17 , it has thus far remained difficult to investigate their individual tissue expression patterns. Rare AMDassociated coding variants in CFH and their functional consequences directly implicate FH in the pathogenesis of AMD 5,12,[18][19][20][21][22] . The molecular basis of the association of FH/ FHL-1 402H variant to AMD pathology has been reported to involve altered binding to heparan sulfate, C-reactive protein or malondialdehyde, impacting local complement activation and subretinal inflammation [23][24][25][26] .…”
mentioning
confidence: 99%
“…Die Krankheit ist durch einen fortschreitenden Verlust des zentralen Sehvermögens gekennzeichnet. Letzteres wird durch die Degeneration von Photorezeptorzellen in der Makula infolge der Bildung sogenannter Drusen verursacht, die die Ansammlung von Retinaabfallprodukten in und um die Bruch-Membran darstellen [103,107]. Dabei werden 2 Formen der AMD unterschieden: Die "trockene" AMD ist durch eine geografische Netzhautatrophie gekennzeichnet, die mit einer allmählichen Degeneration von Photorezeptoren und Pigmentepithelzellen der Netzhaut einhergeht, während die Neovaskularisation der Netzhaut mit aberranten Blutgefäßen ein Kennzeichen der "feuchten" AMD darstellt.…”
Section: Komplement-und Altersbedingte Makuladegeneration (Amd)unclassified
“…In einer kürzlich durch-geführten, genomweiten Assoziationsstudie (GWAS) wurden 52 häufige und seltene Genvarianten identifiziert, die unabhängig voneinander mit AMD assoziiert sind [108]. Unter ihnen befindet sich mehr als ein Drittel (19/52) in oder in der Nähe eines Komplementgens [103,105,108,109]. Insbesondere Varianten der Komplementgene CFH, CFI, C2/CFB, C3, C9, CD55 und Vitronectin (VTN) wurden mit einem erhöhten Risiko für die Entwicklung von AMD in Verbindung gebracht [108, 110 -112].…”
Section: Komplement-und Altersbedingte Makuladegeneration (Amd)unclassified